Extraskeletal Chondroma on the Sole of the Foot - Tanawat Vaseenon (2018)
A 47-year-old female presented with a solitary mass located in the plantar region of her left foot. The mass, which she noticed 2 years ago, grew gradually and caused increasing pain when bearing weight. Physical examination showed a 3.5-cm diameter tender nonmobile mass with firm consistency in the midplantar region. Radiographs showed a ring-like calcification compatible with cartilage tissue. Magnetic resonance imaging revealed a lobulated mass with a hypointense signal on T1-weighted images and a hyperintense signal on T2-weighted images in the mid-substance of the plantar fascia. After a skin incision was performed, the mass was dissected from the skin and subcutaneous tissue. Then, a marginal excision was performed. The histological assessment reported chondrocytes within lacunae embedded in a chondroid matrix with focal calcification. The definitive diagnosis was extraskeletal chondroma. Plantar pain resolved within 3 months and no recurrence was found at the 1-year follow-up.Level of Evidence: Therapeutic Level IV, Case Report © 2013 The Author(s).